Perilaku Muzakki dalam Membayar Zakat Melalui Transaksi Non-Tunai di Lembaga Inisiatif Zakat Indonesia (IZI) Surabaya - Zahriyah Nurul Aini dkk. (Iqtishodia: Jurnal Ekonomi Syariah, 2018)
This research aims to find muzakki’s behavior on paying zakah using non-cash transaction on foundation of Inisiatif Zakat Indonesia (IZI) branch Surabaya. The result of this research shown that muzakki’s behavior in paying zakah using non-cash transaction based of some factors which are behavior based on muzakki’s conviction, behavior based on environment, behavior based on conscious interests, behavior based on spontaneous interests (reflex motion), and behavior based on external factors. Paying zakat which done by informan caused a positive impact towards their life, such as feeling peace, happiness, trusted in office and also in form of great achievements of their children in the school.